Scientific Diplomacy as an Element of the Cold War - K. O. Kolpakov (Vestnik MGIMO-Universiteta, 2021)
Book review: Wolfe A. 2018. Freedom’s Laboratory: The Cold War Struggle for the Soul of Sci- ence. Baltimore: Johns Hopkins University Press. 312 p. ISBN: 9781421426730